Understanding R Gene Evolution in Brassica - Fangning Zhang; Ting Xiang Neik; Tingting Wu; David Edwards; Jacqueline Batley (Agronomy, 2022)
Brassica crop diseases caused by various pathogens, including viruses, bacteria, fungi and oomycetes, have devastating effects on the plants, leading to significant yield loss. This effect is worsened by the impact of climate change and the pressure to increase cultivation worldwide to feed the burgeoning population. As such, managing Brassica diseases has become a challenge demanding a rapid solution. In this review, we provide a detailed introduction of the plant immune system, discuss the evolutionary pattern of both dominant and recessive disease resistance (R) genes in Brassica and discuss the role of epigenetics in R gene evolution. Reviewing the current findings of how R genes evolve in Brassica spp. provides further insight for the development of creative ideas for crop improvement in relation to breeding sustainable, high quality, disease-resistant Brassica crops.